From Knowledge to Peace: The Role of Islamic Education in Cultivating Human Mindset for a Harmonious World - Aiyetoro, Abdulkareem Idris (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2025)
The prevalence of different ideologies and conflicts worldwide underscores the importance of critically exploring the role of education in fostering peace and harmony. Islamic education, grounded in principles derived from Islamic teachings, is significant in cultivating values essential for nurturing a mindset conducive to peace. It is essential to recognise that Islamic education is inclusive, respectful, and values individuals regardless of their religion, ethnicity, or cultural background. Therefore, this paper aims to examine the role of Islamic education in fostering peace and harmony and develop a framework for peacebuilding from the perspective of Islamic education. The study employs a qualitative content analysis design by systematically reviewing relevant literature on Islamic education to investigate its role in promoting global peace and harmony. The findings indicate a comprehensive role of Islamic education, grounded in four main factors: knowledge acquisition, establishing principles of peace, teaching values of peace, and encouraging interfaith dialogue. In addition, the findings also show that rote learning (memorisation) and misconceptions of jihad are potential challenges to Islamic education. Therefore, institutions should incorporate comprehensive peace education into the curriculum, encompassing peace principles and values, Prophetic peace strategies, and other interdisciplinary studies such as conflict resolution skills and international relations. This study recommends that educational policymakers develop and support interfaith initiatives to foster dialogue, understanding, and cooperation between religious communities.